Peran Brand Awareness, Brand Trust, E-Wom dan Online Customer Review Terhadap Keputusan Pembelian Produk Kecantikan - Rahmah, Aulia; Tis’a Ramadhani, Septi Mariani; Anggraeni, Tia Chisca (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Curently, the level of public awareness of health and facial appearance is growing in society, this causes the development and need for beauty products to increase. Wardah is ranked first in the South East Asian's Top Beauty Brand category. The purpose of this study was to analyse the effect of brand awarenes, brand trust, Electronic Word of Mouth (E-WOM) and online customer reviews both simultaneously and partially on purchasing decisions for Wardah beauty products. And to find out the most dominating variable in influencing purchasing decisions for Wardah beauty products. This research data uses primary data, with data collection techniques through distributing questionnaires using Google Form to 130 respondents who have purchased Wardah beauty products in the Jabodetabek area. The analytical tools used in this study consist of descriptive analysis, instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test. The results of the study show that brand awareness, brand trust, and E-WOM have a partial effect on purchasing decisions for Wardah beauty products. Meanwhile, the online customer review variable does not have a partial effect on purchasing decisions for Wardah beauty products. The variables of brand awareness, brand trust, E-WOM and online customer reviews simultaneously influence purchasing decisions for Wardah beauty products.